2018
DOI: 10.32582/aa.59.1.11
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of the digenean Otodistomum veliporum in the spiracle of the kitefin shark Dalatias licha

Abstract: The presence of the digenean Otodistomum veliporum is reported here for the first time as a parasite in the spiracle of a Mediterranean specimen of the kitefin shark Dalatias licha. SAŽETAKPrvi put je zabilježena u znanstvenoj literaturi prisutnost parazita Otodistomum veliporum u štrcalu morskog psa drkovne Dalatias licha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The presence of other parasites, such as nematodes (Anisakis simplex and Raphidascaris sp. ), has been previously reported in other Mediterranean kitefin sharks (Henderson et al, 2003) as well as the presence of Hexabothriids (Kheddam et al, 2016), monogeneans (Septitrema lichae in nasal tissue; Kheddam et al, 2020), and digenean trematodes (Otodistomum veliporum; Sperone and Milazzo, 2018). However, this is the first study reporting the presence of flatworms as endoparasites of the kitefin shark.…”
Section: B a Figurementioning
confidence: 48%
“…The presence of other parasites, such as nematodes (Anisakis simplex and Raphidascaris sp. ), has been previously reported in other Mediterranean kitefin sharks (Henderson et al, 2003) as well as the presence of Hexabothriids (Kheddam et al, 2016), monogeneans (Septitrema lichae in nasal tissue; Kheddam et al, 2020), and digenean trematodes (Otodistomum veliporum; Sperone and Milazzo, 2018). However, this is the first study reporting the presence of flatworms as endoparasites of the kitefin shark.…”
Section: B a Figurementioning
confidence: 48%
“…According to our results, the only O. veliporum specimen found suggests a low density of populations of intermediate hosts in the diet of H. griseus present in the Strait of Messina. Recently, Sperone and Milazzo [57] described O. veliporum in kitefin shark (Dalatias licha, Bonnaterre, 1788) from the Southern Tyrrhenian Sea (Central Mediterranean Sea). In this case, the authors reported one O. veliporum specimen, attached to the mucosa of a D. licha spiracle.…”
Section: Discussionmentioning
confidence: 99%
“…Management efforts from local to regional domains thus require an ocean observation system that monitors marine life in key areas (Costello et al, 2017). Calabria lies in the centre of the Mediterranean, between the Tyrrhenian and the Ionian seas and, together with Sicily and the Tunisian coast, divides the Mediterranean Sea into western and eastern parts (Sperone et al, 2012). Within the region, the Strait of Messina is very important because together with the Sicily-Tunisian Ridge it is one of the two conjunction points between the western and the eastern basins of the Mediterranean Sea for both native and non-native species (Sperone et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Within the region, the Strait of Messina is very important because together with the Sicily-Tunisian Ridge it is one of the two conjunction points between the western and the eastern basins of the Mediterranean Sea for both native and non-native species (Sperone et al, 2015). For these reasons, the position of Calabria is strategic to collect data about chondrichthyans that historically occurred in the entire Mediterranean Sea, and a monitoring program of the University of Calabria has been collecting data on occurrence of the cartilaginous fishes in this important biogeographic area since 2000 (Sperone et al, 2012;Sperone & Milazzo, 2018;. Distribution, ecology, and biology of these fishes are little known for this region, especially for some charismatic and endangered species, such as the white shark (Huveneers et al, 2018;Leone et al, 2020;Mancusi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%